2022
DOI: 10.1186/s12916-021-02230-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the diagnostic accuracy of prostate-specific antigen (PSA) for the detection of prostate cancer in symptomatic patients

Abstract: Background Prostate-specific antigen (PSA) is a commonly used test to detect prostate cancer. Attention has mostly focused on the use of PSA in screening asymptomatic patients, but the diagnostic accuracy of PSA for prostate cancer in patients with symptoms is less well understood. Methods A systematic database search was conducted of Medline, EMBASE, Web of Science, and the Cochrane library. Studies reporting the diagnostic accuracy of PSA for pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 50 publications
3
32
0
1
Order By: Relevance
“…The performance of the integrated risk model is similar to the diagnostic accuracy of PSA as reported in the literature: AUC 0.72 (95% CI 0.68-0.76) [12]. We hypothesise that the optimal predictive model would incorporate PSA, GRS, and other clinical features.…”
Section: Comparison To the Existing Literaturesupporting
confidence: 75%
See 2 more Smart Citations
“…The performance of the integrated risk model is similar to the diagnostic accuracy of PSA as reported in the literature: AUC 0.72 (95% CI 0.68-0.76) [12]. We hypothesise that the optimal predictive model would incorporate PSA, GRS, and other clinical features.…”
Section: Comparison To the Existing Literaturesupporting
confidence: 75%
“…Only a small proportion of the cohort had a PSA test result on record, and these were abnormal; the AUC for PSA alone was >0.9 which is unrealistic compared to the literature and likely to be the result of ascertainment bias [12]. As PSA is part of the current diagnostic pathway to determine if a patient is investigated for prostate cancer, it has a direct causal effect on whether an individual will be diagnosed with prostate cancer independently of the test's ability to predict that outcome.…”
Section: Variable Definitionmentioning
confidence: 68%
See 1 more Smart Citation
“…This test is far from ideal, however, because even slightly elevated PSA levels can be associated with confounding factors such as benign prostatic hyperplasia (BPH) or prostatitis [ 9 ]. In addition, more than 25% of men with PCa are found to have normal PSA levels [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneous behaviour of prostate cancers, along with the poor performance of prostate specific antigen (PSA) testing in identifying clinically important disease, remain obstacles to implementing beneficial strategies for early diagnosis 34. A systematic review found that PSA screening has little or no effect on prostate cancer mortality (incidence rate ratio 0.96, 95% confidence interval 0.85 to 1.08) and can, at best, prevent one prostate cancer death for every 1000 patients tested over 10 years 5…”
mentioning
confidence: 99%